Pragmatic randomised trial to evaluate the use of patient held records for the continuing care of patients with cancer. Issue 3 (1st September 2001) - Williams, J G; Cheung, W-Y; Chetwynd, N; Cohen, D R; El-Sharkawi, S; Finlay, I; Lervy, B; Longo, M; Malinovszky, K
Abstract : Objective —To evaluate the use of a multidisciplinary record held by patients with cancer in the community. Design —Pragmatic randomised controlled trial. Setting —The environs of Swansea in south west Wales. Participants —501 patients under the care of the Department of Oncology, Singleton Hospital, Swansea. Intervention —A patient held record used by the patient and healthcare professionals. Main outcome measures —Health related quality of life (EORTC QLQ-C30) measured at entry into the study and at 6 months; patients' views at 6 months; healthcare professionals' views collected after the completion of patient follow up; NHS resource and booklet use. Results —1148 patients were eligible for the study; 501 were recruited (44%) and 344 completed the study (172 in each group). There was no significant difference between the two groups in change in quality of life or NHS resource use. The patient held record did not have an impact on communication but was significantly helpful to patients in preparing for appointments, reducing difficulties in monitoring their own progress, and helping them to feel more in control (p<0.05). Fifty three percent of patients would have preferred not to have a patient held record. There was a low level of use of the record by healthcare professionals but most of those who remembered using it indicated that they would prefer patients to have it. Conclusions —The patient held record is valued by some patients and professionals but has no significant impact on the quality of life of patients or NHS resource use. It has a positive impact on quality by helping patients feel more in control and prepare for meetings with healthcare staff. Patients who find it useful tend to be younger and have more professionals involved in their care. It is recommended that it should be made available to patients on request and used by them according to need.